Pijat Kehamilan untuk Menurunkan Stres Psikologi pada Kehamilan Remaja dan Implikasinya terhadap Pencegahan Stunting - Tri Purwanti; Fera Yuli Setiyaningsih (EMBRIO: Jurnal Kebidanan, 2022)
Teenage pregnancy is a global problem with a very high number, where the risk of giving birth to stunting children is 2.74 times compared to woman who gives birth at reproductive age. This type of research is a quantitative analysis using Quasi Experiment design with One group pre-post test design method. The independent variable is pre natal massage and the dependent variable is the stress of pregnant women in the third trimester and stunting of newborns. The sample in this study were all 15 pregnant women during the third trimester PMB Lilis Surya Wati, Sariloyo Hamlet, Sambongdukuh Village, Jombang Regency. Data analysis using SPSS software with Wilcoxon statistical test. The results of the analysis test showed a significant relationship between the frequency of prenatal massage and the risk of stunting. The result which obtained a significant value of 0.002 (p< 0,05), so it could be concluded that the frequency of prenatal massage that was more frequent reduced stress and the risk of stunting a significant < 0.002. There is an effect of prenatal massage to reduce psychological stress in teenage pregnancy and its implications for stunting prevention